Identifying dendritic cell heterogeneity and potential risk genes in atopic dermatitis: integrative scRNA-seq, bulk RNA-seq analyses and experimental validation - Chushan Huang; Pengsheng Chen; Xiaosong Chen (Frontiers in Medicine, 2026)
Atopic dermatitis (AD) is a chronic inflammatory skin condition marked by immune dysregulation and compromised skin barrier function, with dendritic cells (DCs) playing pivotal roles in its pathogenesis. This study aimed to systematically characterize the heterogeneity of DCs in AD, identify key pathogenic subsets and genes, and elucidate their regulatory mechanisms through advanced methodologies. We conducted integrated single-cell RNA sequencing (scRNA-seq) analyses on both AD lesions and normal skin samples, leading to the identification and functional annotation of distinct DC subtypes. Through deconvolution, pseudotime trajectory, and co-expression network analyses, we screened critical cell populations and candidate genes. Causal associations were assessed using Mendelian randomization and colocalization analyses, while transcription factor activity inference, kNN-DREMI, and motif analysis were employed to explore underlying regulatory mechanisms. Our results revealed five distinct DC subsets, with a notable expansion of CD207 + migratory DCs ( CD 207 m DC ) inADlesi ons, contrasting with the enrichment of IL1B + DCs in normal skin. CD207_mDCs exhibited enhanced migratory and antigen-presenting capabilities, with CD1B being significantly upregulated and uniquely enriched within this subset. Integrative analyses suggest that CD1B may play a role in AD pathogenesis, potentially regulated by NOTCH1 signaling. These findings underscore the critical involvement of CD207_mDCs in AD progression and highlight CD1B as a promising candidate gene, implicating the NOTCH1–CD1B axis in Th2 polarization and presenting novel therapeutic targets for intervention in AD.